A Novel Terminal Sliding Mode Variable Structure Model Reference Adaptive System Observer for Permanent Magnet Synchronous Motors - Yan Bai; Lei Zhang; Xiang-Min Meng; Jing Bai; Guang Han (International Transactions on Electrical Energy Systems)
This paper introduces a model reference adaptive system observer based on the non-singular fast terminal sliding mode (NFSM-MRASO) for the purpose of sensorless control of permanent magnet synchronous motors (PMSMs) in electric vehicle applications. Firstly, a non-singular fast terminal sliding surface is constructed based on the output errors of the reference model and the adjustable model. This ensures that the output errors between the two models converge to zero in a finite time and effectively avoids the singularity problem in the terminal sliding mode control. In addition, a novel reaching law (NRL) is designed to replace the traditional exponential reaching law (TRL) to suppress the chattering phenomenon in the sliding mode control. Finally, the feasibility and effectiveness of the NFSM-MRASO strategy are demonstrated through simulation results.